Fracture resistance to fixed partial denture abutments with direct and indirect posts (Research, Society and Development, 2022)
The objective of this study was to evaluate the resistance to fracture of three-element fixed partial dentof glasstment teeth restored with glass fiber posts (GFP) and cast post-and-core (CPC) retainers. Herein, 60 bovine mandibular incisors were divided into two groups (n = 30) according to the retainer type in: 1) resin composite core reinforced with GFP; and II) CPC (Cu-Al). Each pair of roots consisted of one sample, simulating a three-element fixed partial denture. The structures of the fixed three-element partial dentures were made in Ni-Cr alloy. A conventional dual resin cement (RelyX ARC - 3M Espe, USA) was used for all cementation procedures. Samples were subjected to a compressive load onto an orifice at occlusal contact region of the pontic until collapse or fracture.  Normal data distribution was verified by D'Agostino & Pearson normality test. Unpaired t test was used for data analysis (α = 5%). The results showed that the the three-element fixed partial denture abutment teeth restored with composite resin cores retained by GFP presented higher fracture resistance compared to the ones restored with CPC (p=0.0009). In conclusion, the resistance to fracture of three-element fixed partial denture restored with resin composite core reinforced with glass fiber posts was higher to the one restored with post-and-core retainers.